PERUBAHAN KOMPOSISI JENIS VEGETASI DAN BURUNG SETELAH PENANAMAN KELAPA SAWIT DI LAHAN KERING PELAIHARI KALIMANTAN SELATAN - Kissinger Kissinger; Rina Muhayah Noor Pitri; Hamdani Hamdani (EnviroScienteae, 2016)
Elais guenensis planting programe have changed land cover and compotition of vegetation and animal.  Vegetation changing by E.guenensis planting becomes multiple effect to other sector. The aims of this research are: to describe changing of  land cover and to know changing of vegetation and aves composition after E.guenensis planting.  Teresterial survey had arranged to collected data. Analyze of data used time series data and matrice tabulation, descriptive and comparison. Land coverage changing caused by E.guenensis planting.  Number of tree species vegetation had been changed from: 33 species to 16 species. Number of aves species had been changed from 21 species to 15 species.  Decreasing number and composition of vegetation had influenced decreasing number and composition of aves. Loosing on variation habitat vegetation types which produce food caused population of aves are limited.